An analysis of firm support for active labor market policies in Denmark, Germany, and the Netherlands - Nelson, Moira (Amsterdam, 2009)
"Active labor market policies, defined as programs for marginalized workers that improve their chances of finding stable jobs, have grown in importance since roughly 1980 due to high levels of unemployment. This paper examines the role of private firms in active labor market policies in three generous welfare states—Denmark, Germany and the Netherlands. Whereas the participation of private firms in the implementation of active labor market policies enhances the efficiency of these policies, firms’ increased bargaining power within the national policy-making arena raises questions about their continued willingness to adjust their preferences in order to accommodate public concerns. The results suggest that the state plays a fundamental role in building firm support for active labor market policies, although employer organizations do influence firms’ participation in these programs."